Factors Influencing CRM Technological Initiatives Among Small and Medium-Sized Enterprises in Singapore - Chia, Peng Kiat (2008)
The purpose of this study is to address the low adoption rate of customer relationship management (CRM) technology among small and medium-sized enterprises (SMEs) in Singapore. Such an understanding will be useful for SMEs' managers, IT consultants, vendors and government agencies in drawing guidelines on how to encourage and motivate widespread adoption of CRM technology to empower Singapore's SMEs to compete in the global business environment. The study examines the effect of eight independent variables on the intention to adopt CRM. A review of the literature shows that innovation characteristics: relative advantage, compatibility, complexity and cost effectiveness; organisational characteristics: top management support and information technology (IT) knowledge; and environmental characteristics: government support and competitive pressure are significant factors in influencing SMEs'intention to adopt CRM technology.